(3GdJUQja def YLR Yf GdJCdjas - (3Nda Hf YHGS GdRgQGhqj GdCfOdSj, CHh GdbGSe,J (B427 (3g` s
(3ChdgG (B:s
(3bGd CHh GdbGSe Ef eYQaI bdjd GdCZPjIhGdCOhjI hEUdGMgG def hcjO eG jMJGL Edjg ai UfGYI GdWH s
(3BNQgG (B:s
(3eHJhQ , JfJgi gi CKfGA GdHGH GdNGeS ef GdebGdI GdJGSYI hGdYTQjf ai JaSjQ GdCcjGd hGdChRGf GdehLhOI ai cJHge HGNJdGa dZGJge GdCcjGd hGdChRGf GdJi ChdgG Tjf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B203 - (3U(B466s
(3fSNI NGeSIs
(3JHOC HGdebGdI GdSGHYI hGdYTQjf ai bhi GdCZPjI hGdCOhjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B310 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B105s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B58 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs